1989
DOI: 10.1002/jcb.240390210
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of nuclear and cytoplasmic glycogen isolated from mutant HD33 ascites cells

Abstract: Mutant cells of the HD33 subline of the Ehrlich-Lettré ascites tumor synthesize and store glycogen mainly intranuclearly, when growing in vivo, and exclusively in the cytoplasm, when permanently cultivated as a suspension cell strain. To investigate whether there exist differences between glycogen of nuclear and cytoplasmic origin, the ultrastructure and the biophysical and biochemical properties of glycogen from in vivo and in vitro grown HD33 ascites cells were compared. Pronounced heterogeneity and differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…The electron microscopy showed colloidal gold-labelled immunoreaction in the cytoplasm and nucleus of neuronal cells, which demonstrate the presence of glycogenin in retina neuronal cells and in consequence, the possibility of the de novo glycogen biosynthesis in these cells. The incorporation of glucose into intranuclear glycogen was described in HD33 ascites tumor cells (13) and the chemical characterization of the HD33 intranuclear polysaccharide was also reported (14). Our results show glycogenin in the nucleus of Figure 5: Immunoaold cytochemical labelling of glyc0genin in sections of the inner plexiform and optic fiber layers.…”
Section: Discussionsupporting
confidence: 78%
“…The electron microscopy showed colloidal gold-labelled immunoreaction in the cytoplasm and nucleus of neuronal cells, which demonstrate the presence of glycogenin in retina neuronal cells and in consequence, the possibility of the de novo glycogen biosynthesis in these cells. The incorporation of glucose into intranuclear glycogen was described in HD33 ascites tumor cells (13) and the chemical characterization of the HD33 intranuclear polysaccharide was also reported (14). Our results show glycogenin in the nucleus of Figure 5: Immunoaold cytochemical labelling of glyc0genin in sections of the inner plexiform and optic fiber layers.…”
Section: Discussionsupporting
confidence: 78%
“…In fact, a number of studies have reported glycogen in association with the nuclear envelope, the endoplasmic reticulum, and the annulate lamellae of embryonic and transformed cells [14,[39][40][41]. Glycogen has also been reported inside the nucleus [42][43][44][45][46]. Moreover, glycogen consistently appears in the Xenopus embryo during the cleavage stage [47].…”
Section: Discussionmentioning
confidence: 94%
“…A number of studies have reported glycogen in association with the nuclear envelope, the endoplasmic reticulum, and with annulate lamellae of embryonic and transformed cells (Coimbra and Lebland, 1966;Flaks, 1968;Eyal-Giladi et al, 1985;Kessel, 1989;Hubbard et al, 1990;Kessel and Beams, 1990). Glycogen has also been reported inside the nucleus (Himes and Pollister, 1962;Karasaki, 1971;Mori et al, 1970;Granzow et al, 1981;Kopun et al, 1989; for a review of intranuclear glycogen see Ferrans et al, 1975). These reports of glycogen in close apposition with nuclear envelopes and annulate lamellae may represent a structural association, or merely a circumstantial association.…”
Section: Models For Glycogen Activitymentioning
confidence: 98%